Genome-wide association study of esophageal squamous cell carcinoma in Chinese subjects identifies susceptibility loci at PLCE1 and C20orf54 - WANG, Li-Dong; ZHOU, Fu-You; ZHANG, Lian-Qun; YANG, Jie-Zhi; LI, Ji-Lin; LI, Xing-Chuan; REN, Jing-Li; LIU, Zhi-Cai; GAO, Wen-Jun; LING YUAN; WUWEI; ZHANG, Yan-Rui; et al. (Nature genetics, 2010)
We performed a genome-wide association study of esophageal squamous cell carcinoma (ESCC) by genotyping 1,077 individuals with ESCC and 1,733 control subjects of Chinese Han descent. We selected 18 promising SNPs for replication in an additional 7,673 cases of ESCC and 11,013 control subjects of Chinese Han descent and 303 cases of ESCC and 537 control subjects of Chinese Uygur-Kazakh descent. We identified two previously unknown susceptibility loci for ESCC: PLCE1 at 10q23 (P(Han combined for ESCC) = 7.46 x 10(-56), odds ratio (OR) = 1.43; P(Uygur-Kazakh for ESCC) = 5.70 x 10(-4), OR = 1.53) and C20orf54 at 20p13 (P(Han combined for ESCC) = 1.21 x 10(-11), OR = 0.86; P(Uygur-Kazakh for ESCC) = 7.88 x 10(-3), OR = 0.66). We also confirmed association in 2,766 cases of gastric cardia adenocarcinoma cases and the same 11,013 control subjects (PLCE1, P(Han for GCA) = 1.74 x 10(-39), OR = 1.55 and C20orf54, P(Han for GCA) = 3.02 x 10(-3), OR = 0.91). PLCE1 and C20orf54 have important biological implications for both ESCC and GCA. PLCE1 might regulate cell growth, differentiation, apoptosis and angiogenesis. C20orf54 is responsible for transporting riboflavin, and deficiency of riboflavin has been documented as a risk factor for ESCC and GCA.